2022
DOI: 10.3389/fneur.2022.914411
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Complications of SARS-CoV-2 and Other Viral Infections

Abstract: In this article we review complications to the peripheral nervous system that occur as a consequence of viral infections, with a special focus on complications of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). We discuss neuromuscular complications in three broad categories; the direct consequences of viral infection, autoimmune neuromuscular disorders provoked by viral infections, and chronic neurodegenerative conditions which have been associated with viral infections. We also include discussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 240 publications
(309 reference statements)
1
10
0
Order By: Relevance
“…COVID-19 is a complex infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Clinical evidence has shown that the main symptoms of COVID-19 can include acute infection of the respiratory tract, as well as inflammatory reactions of multiple organs [ 21 , 22 ]. SARS-CoV-2 enters cells by first binding to angiotensin-converting enzyme 2 (ACE2), followed by cleavage of the virus spike protein by transmembrane protease serine 2 (TMPRSS2) [ 23 ].…”
Section: Research Progress Of Nrf2 In Inflammation-related Diseasesmentioning
confidence: 99%
“…COVID-19 is a complex infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Clinical evidence has shown that the main symptoms of COVID-19 can include acute infection of the respiratory tract, as well as inflammatory reactions of multiple organs [ 21 , 22 ]. SARS-CoV-2 enters cells by first binding to angiotensin-converting enzyme 2 (ACE2), followed by cleavage of the virus spike protein by transmembrane protease serine 2 (TMPRSS2) [ 23 ].…”
Section: Research Progress Of Nrf2 In Inflammation-related Diseasesmentioning
confidence: 99%
“…Several human picornaviruses are associated with neurological motor disturbances, including poliovirus and coxsackievirus B3 [ 193 ]. A picorna-like virus called Nora virus has recently been shown to cause locomotor disturbance in Drosophila [ 194 ].…”
Section: Neuroinfection and Neuroimmunity Models In Drosophilamentioning
confidence: 99%
“…Neurological symptoms have been frequently reported in patients infected with severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) [ 193 , 213 ], the causative agent of COVID-19. Presentations can range from a loss of taste and smell, seizures, stroke, epilepsy, meningitis/encephalitis and motor disturbances.…”
Section: Neuroinfection and Neuroimmunity Models In Drosophilamentioning
confidence: 99%
“…Infectious diseases such as human immunodeficiency virus (HIV) and tuberculosis are also more prevalent among Indigenous people in Canada [11,12]. This is relevant to neurologic disease because of the strong association of HIV with various neurologic presentations [13]. Tuberculosis may also infect the nervous system, can be very difficult to recognize clinically, and requires prolonged treatment [14].…”
Section: Health Equity In Neurosciencesmentioning
confidence: 99%
“…It is associated with high mortality particularly when co-existing HIV infection is present [14]. The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic may have also disproportionately affected Indigenous communities [15], which is of major importance due to the various neurological complications which have been reported in association with SARS-CoV-2 [13,16]. Recently, we also became aware that a neurogenetic condition (Kennedy disease, or spinal bulbar muscular atrophy) is highly prevalent among Indigenous people living in prairie provinces [17].…”
Section: Health Equity In Neurosciencesmentioning
confidence: 99%